A Missense Mutation in the UGDH Gene Is Associated With Developmental Delay and Axial Hypotonia - Alhamoudi, Kheloud M.; Bhat, Javaid; Nashabat, Marwan; Alharbi, Masheal; Alyafee, Yusra; Asiri, Abdulaziz; Umair, Muhammad; Alfadhel, Majid (Frontiers in Pediatrics, 2020)
UDP-glucose dehydrogenase (UGDH) encodes an oxidoreductase that converts two successive oxidations of UDP-glucose to produce UDP-glucuronic acid, a key component in the synthesis of several polysaccharides such as glycosaminoglycan and the disaccharide hyaluronic acid. UGDH is critical to the production of extracellular matrix components which are essential to the migration and connectivity of neurons early in human brain development. In this report, we describe one child of a consanguineous family who presented with distinct clinical features including global developmental delay, axial hypotonia, bilateral undescended testis, and subtle dysmorphic features. Whole genome sequencing and a segregation was performed to identify the genetic cause of the disease within the family. Though mutations in the UGDH protein have been described as causing developmental delay in various model organisms, herein the identification of the novel homozygous missense variant in exon8 of UGDH NM_003359.3: c.950 G>A (p.Arg317Gln) is most likely the cause of the patient’s phenotype. This variant falls in an active region and replaces the highly conserved Arginine 317 residues across mammals.